Legal Analysis of Justice-Based Criminalization of Perpetrators of Domestic Violence (Case Study Number 1/Pid.Sus/2025/Pn Tjt) - Sefriana Fajar; Arpangi Arpangi (UNISSULA Semarang, 2025)
Abstract. Harmony and integrity within a household can be disrupted if self-quality and self-control are not maintained. This condition has the potential to give rise to domestic violence which results in feelings of insecurity and injustice for family members. Therefore, the state and society have an obligation to undertake preventive measures, provide protection to victims, and prosecute perpetrators in accordance with the values of Pancasila and the mandate of the 1945 Constitution of the Republic of Indonesia. Legal development is not only limited to formulating rules, norms, or principles, but must be carried out systematically and comprehensively. This includes thorough legal planning, the formation of new regulations based on Pancasila and the 1945 Constitution of the Republic of Indonesia, the implementation and provision of quality legal services, and effective and efficient law enforcement, while still upholding humanitarian values. Essentially, criminal law reform is a concrete manifestation of changes and improvements to various aspects and policies that form its background. Therefore, a planned and systematic legal development is needed to accelerate the renewal and formation of the existing legal system in Indonesia. Law Number 23 of 2004 concerning the Elimination of Domestic Violence was ratified in Jakarta on September 22, 2004 and signed by Megawati Soekarnoputri as the President of the Republic of Indonesia at that time. Law Number 23 of 2004, which is often referred to as the PKDRT Law, firmly states that every citizen has the right to live safely and free from all forms of violence, based on the values of Pancasila and the 1945 Constitution. The main objective of this regulation is to eliminate the practice of domestic violence while creating a balance of position between husband and wife, children and parents, as well as between the nuclear family and parties involved in household life, which is an important factor in preventing domestic violence.